دراسة وتقييم فعالية محطة مياه المقرن - أحمد هاشم حسن إدريس; عاصم علي عوض عبدالله; مازن محسن إدريس الضو (جامعـــــــــة الشيــخ عبــد الله البــدري, 2018)
تناولت الدراسة تقيم جودة مياه محطة المقرن , تمثلت مشكلة الدراسة في الأتية: عكارة عالية في شهور الفيضان من أول مايو حتي سبتمبر , إستهلاك عالي يفوق طاقة المحطة في الصيف , تكاثر الطحالب في الخريف , هدفت الدراسة الي تقييم نوعية مياه الشرب بالمحطة و ذلك بإجراء الإختبارات المعملية لمياه المأخذ و مياه الشبكه ومقارنتها مع المواصفات العالمية والسودانية لمياه الشرب , معاينة أجزاء المحطة و فعاليتها وفقاً لغيرها , مقارنة بتقييم المحطات المثالية , حساب كميات المياه النقية من المحطة و مقارنتها بالإحتياجات الفعلية , دراسة مشكلة الطحالب وإيجاد الحلول حيث حللت العينات وفقاً للطرق القياسية المستخدمة في تحليل مياه الشرب بإجراء الإختبارات الفيزيائية و الكيميائية و البكترلوجية ( العكارة , الموصلية الكهربائية , درجه تركيز المواد الصلبة , الرقم الهايدروجيني , أيون الكلورايد , العسر الكلي , العدد الكلي للبكتريا , المجموعة القولونية ). توصلت الدراسة إلي عده نتائج أهمها : أن مشكلة الطحالب لازالت قائمة ولا توجد طريقة لإزالتها إلا يدويا , أن المياه المتاحة مقدارها 90000m3/day, بينما المطلوب للإستعمال هو 120000m3/day , مشكلة العكارة ملازمة للمنطقة عامةً و في فتره الفيضان خاصة. بناءً علي نتائج الدراسة قدم الباحثون عده توصيات أهمها: لابد من إنشاء محطة جديدة ليتم الأكتفاء من مياه المحطة الحالية , و للعلم يتم توسعه للمحطة الحالية , العكارة عالية في أيام القيضان لابد من حلها حلاً عاجلاً لتفادي الأمراض و كذلك التخلص من الطحالب , لابد من مزيد من الدراسة لمحطة المقرن إذ أنها تمثل أهم محطات مياه الشرب للعاصمة. Abstract The study with the water quality of AL¬-Muqrin station. The problem of The study represented in the following: High turbidity in the flood months from May 1 to September. High consumption outweighs the power of the station in the summer, the growth of algae in autumn, The study aimed to evaluate the quality of drinking water in the station by conducting Laboratory test of water of the intake and the water of the network and comparing it with scientific and Sudanese specifications of drinking water, inspection of the scientific and their effectiveness according to others, compared to the evaluation of the ideal stations. Calculate the quantities of pure water from the station and compare it to actual needs. The analysis of algae problem and the solution of the solutions were analyzed according to the standard methods used in drinking water analysis by physical. Chemical and bacteriological tests (turbidity, electrical conductivity, concentration of solids, ph, chloride, total hardness, total number of bacteria, coliform group). The study reached several results, the most important of them are: The problem of algae is still there and there is no way removes it, except manually. The available water is 90000m3/day, while the required for use is 120000m3/day, the problem of turbidity is inherent to the area in general and during the flood period especially. Based on the results of the study, the researchers made several recommendations, the most important of them are: A new station must be established to be satisfied with the current station water , and if that is not possible the expansion of the existing current station could be done . High turbidity in the days of flood must be resolved sooner to avoid diseases as well as disposal of algae. Further study is required of AL-Muqrin station as it represents the most important drinking water station for the capital.